The effects of diaphragm components in resisting lateral stability of precast concrete frames - Abd. Rahman, Ahmad Baharuddin; Rais, Ahmad Zaidon (Universiti Teknologi Malaysia, 2005)
Frame system structures which composed of only reinforced concrete columns, beams and slabs, have been recently adopted for many framed buildings. Generally, flexural stiffness of slabs is ignored in the conventional analysis of bare frame structures. However, in reality, the floor slabs may have some influence on the lateral response of the structures. Consequently, if the flexural stiffness of slabs in a frame system structure is totally ignored, the lateral stiffness of the global frames may be underestimated. Therefore, the objective of the research is to investigate the effects of floor diaphragms in multi-storey frames by comparing the two models of frames with slabs and without slabs. The results show that the slabs can slightly increase the lateral stability of bare frames by about 10% to18%. Furthermore, it can be seen from the study that the main important role of the slab is actually to act as a deep beam in transferring the horizontal loads from the slabs to the columns.